Variability in the Drug Response of M4 Muscarinic Receptor Knockout Mice During Day and Night Time - Valuskova, Paulina; Riljak, Vladimir; Forczek, Sandor T.; Farar, Vladimir; Myslivecek, Jaromir (Frontiers in Pharmacology, 2019)
Mice are nocturnal animals. Surprisingly, the majority of physiological/pharmacological studies are performed in the morning, i.e., in the non-active phase of their diurnal cycle. We compared the effects of scopolamine, oxotremorine, and cocaine on locomotor response, hypothermia and spontaneous behaviour in the open field arena in the morning (9:00 AM) and in the evening (9:00 PM) in C57Bl/6NTac wild type mice (WT) and in C57Bl/6NTac mice lacking the M4 muscarinic receptors (M4KO). Furthermore, we also studied morning vs. evening densities of muscarinic, GABAA, D1-like, D2-like, NMDA and kainate receptors using autoradiography in the motor, somatosensory and visual cortex and in the striatum, thalamus, hippocampus, pons, and medulla oblongata. At 9:00 AM, scopolamine induced a 2.5-fold increase in motor activity in WT and a 3.5-fold increase in M4KO, yet no significant increase was observed at 9:00 PM. Oxotremorine induced hypothermic effects in both WT and M4KO, and those effects were more pronounced at 9:00 AM than at 9:00 PM and in WT than in M4KO. Cocaine increased motor activity in both WT and M4KO at both 9:00 AM and 9:00 PM; nevertheless, the latter increase (9:00 PM) was not as high. There was no difference in behaviour in the open field between WT and M4KO when tested at 9:00 AM; however, at 9:00 PM, activity of M4KO was doubled in comparison to that of WT. Autoradiography revealed no significant morning vs. evening difference. Altogether, our results indicate the necessity of comparing morning vs. evening drug effects.